2013
DOI: 10.1039/c3cp52504j
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble and ligand effects on the acetylene adsorption on ordered PdxAg1−x/Pd(100) surface alloys investigated by periodic DFT study

Abstract: The interactions of acetylene with structurally ordered PdxAg1-x/Pd(100) (x = 1, 0.75, 0.5, 0.25) surface alloys, in which Ag is presented only in the first layer as the computational model system, were investigated by gradient corrected periodic density functional calculations to unravel and understand contributions from electronic strain, electronic ligand and geometric ensemble effects. The calculated adsorption energies indicate that the hollow sites are always found to be more stable than any others and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…While Ga atom becomes less positive changing from 0.893e -to 0.656e -. The negative value of work function change, indicates that, in the presence of the acetylene molecules, the electrons are easily extracted from the surface, which also indicates that the adsorption is dominated by donation rather than backdonation effects 48 Figure 1. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 We also computed the stretching vibration frequencies for the adsorbed C 2 H 2 .…”
Section: Resultsmentioning
confidence: 95%
“…While Ga atom becomes less positive changing from 0.893e -to 0.656e -. The negative value of work function change, indicates that, in the presence of the acetylene molecules, the electrons are easily extracted from the surface, which also indicates that the adsorption is dominated by donation rather than backdonation effects 48 Figure 1. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 We also computed the stretching vibration frequencies for the adsorbed C 2 H 2 .…”
Section: Resultsmentioning
confidence: 95%
“…These findings clearly demonstrate that the most desirable structure of a highly dilute alloy surface depends on the application we are interested in. It is established that the adsorption behavior on alloy catalysts is rationalized through the so-called ensemble and ligand effects. These effects are related to the composition and electronic structure of the active site, respectively, and determine, to a large extent, the nature of the active site. It then follows that if one could possibly find a way to engineer the architecture of the surface of highly dilute alloys, one would be able to optimize their catalytic performance according to the needs of any particular application.…”
Section: Introductionmentioning
confidence: 99%
“…Then the generated H a spills from Pd sites to adjacent Ag metal sites. [ 65,85‐87 ] It has been revealed that the Ag sites do not adsorb alkynes and alkenes and the binding energy of spilled H a on them is less than that of Pd sites. [ 66,88‐89 ] The spilled H a species on Ag sites tend to flow back to the Pd sites and facilitate the hydrogenation of alkynes or alkenes absorbed on Pd sites.…”
Section: Resultsmentioning
confidence: 99%